2017
DOI: 10.1016/j.jnutbio.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Liquid fructose in Western-diet-fed mice impairs liver insulin signaling and causes cholesterol and triglyceride loading without changing calorie intake and body weight

Abstract: LFS in mice, in a background of an unhealthy diet that already induces fatty liver visceral fat accretion and obesity, increases liver lipid burden, hinders hepatic insulin signaling and diminishes whole-body insulin sensitivity without changing energy intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
(33 reference statements)
4
15
0
Order By: Relevance
“…This is in agreement with our previous observation of increased CD36 mRNA expression in WF-LDL-R −/− mice [18]. In contrast, our recent study performed in wild type C57BL/6N mice, showed no signs of hepatic inflammation despite a significant increase in hepatic cholesterol deposition in W and WF groups [17]. To compare the hepatic cholesterol deposition between wild type and knockout mice, we used data from [17,18], and expressed them as mg of cholesterol per gram protein.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This is in agreement with our previous observation of increased CD36 mRNA expression in WF-LDL-R −/− mice [18]. In contrast, our recent study performed in wild type C57BL/6N mice, showed no signs of hepatic inflammation despite a significant increase in hepatic cholesterol deposition in W and WF groups [17]. To compare the hepatic cholesterol deposition between wild type and knockout mice, we used data from [17,18], and expressed them as mg of cholesterol per gram protein.…”
Section: Discussionsupporting
confidence: 92%
“…However, it has been suggested that insulin sensitivity is not reduced when the inflammation is restricted to the liver compartment and does not affect adipose tissue [1,11,41]. Our results are in accordance with this hypothesis, as LDL-R −/− mice show no signs of inflammation in vWAT (Figure 1), whereas in our previous study in wild type mice we observed inflammation in vWAT but not in the liver, and whole-body insulin sensitivity was significantly reduced [17]. …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations